INTERCROP AND IRRIGATION EFFECTS ON DRY MATTER PRODUCTION AND PARTITIONING IN ELEPHANT FOOT YAM (Amorphophallus paeoniifolius Amorphophallus paeoniifolius (Dennst.) NICOLSON) - S.K. JATA; M. NEDUNCHEZHIYAN; S.K. MAITY; M. MALLIKARJUN (The Bioscan, 2019)
The field experiment was conducted during 2012 and 2013 at the Regional Centre of ICAR-Central Tuber Crops Research Institute, Dumuduma, Bhubaneswar, Odisha to study the effects of intercrop and drip irrigation on dry matter production and partitioning in elephant foot yam [Amorphophallus paeoniifolius (Dennst.) Nicolson]. The experiment was laid out in split plot design with five replications. The treatments consisted of C1-elephant foot yam + green gram and C2-elephant foot yam sole crop in main plots and I1-surface irrigation, I2-drip irrigation at 100% cumulative pan evaporation (CPE), I3-drip irrigation at 80% CPE and I4-drip irrigation at 60% CPE in sub-plots. Under intercropping the elephant foot yam corm sprouted earlier than sole cropping. The pseudostem and corm dry matter production, and corm bulking rate was higher for elephant foot yam + green gram intercropping which led to greater corm yield than sole cropping. Drip irrigation at 100% CPE and 80% CPE resulted in earlier sprouting of elephant foot yam which led to greater pseudo stem and corm dry matter production, corm bulking rate and corm yield. Considering the corm yield of elephant foot yam as well as importance and availability of water, green gram can be grown as intercrop in elephant foot yam with the application of drip irrigation at 80% CPE.